Penyusunan Sistem Informasi Akuntansi Nonlaba (Studi Kasus Pada Pondok Pesantren Raudlotul Qur’an) - Liafatra Nurlaily; Ayu Nurafni Octavia; Ahmad Sahri Romadon (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to determine the situation of financial recording and the information management system in the Raudlotul Qur'an Islamic boarding school, then produces a proposal for a financial information management system in the form of an accounting information system design by SAK ETAP and ISAK 35 which has been adapted to the conditions of the boarding school. A single case study approach was applied and carried out observations, interviews, literature studies, and documentation of the data. The research results obtained were that treasurers recorded using the single entry method, there was no clear division of duties and authority among the treasurers, financial recording and reporting were not carried out in an orderly and consistent manner. Therefore, the researcher proposes the division of duties and authority of the treasurer, a flow chart of receipts and disbursements, the evidence to be available for each transaction, proposed account and financial report formats. Key words: accounting information system, Islamic boarding school financial reports, SAK ETAP, ISAK 35, accountability.